Geographic distribution of the earthquakes included in the catalog of National Seismological Network of Costa Rica - Godínez-Rodríguez, Kevin; Arroyo-Solórzano, Mario; Linkimer-Abarca, Lepolt (Revista Geográfica de América Central., 2018)
This article analyzes the time-geographic distribution of earthquakes in Costa Rica for the seismicity included in the catalog of the Red Sismológica Nacional (National Seismological Network) during 1975-2014. The geographic distribution of seismicity highlights the main active tectonic structures. In particular, clusters of seismicity reveal highly deformed crustal areas, which are located along the inland projected path of seamount chains and the Panama Fracture Zone. These clusters do not correlate exactly with the largest energy released zones. A seismic gap is also detected in the Talamanca mountain range. The inspection of seismicity based on the political division of the country shows that the county with the largest amount of recorded earthquakes is Pérez Zeledón, and the counties with the highest earthquake density are: Parrita, El Guarco, Tarrazú, León Cortés, and Desamparados.